1988
DOI: 10.1113/jphysiol.1988.sp016922
|View full text |Cite
|
Sign up to set email alerts
|

Two long‐lasting central respiratory responses following acute hypoxia in glomectomized cats.

Abstract: SUMMARY1. Central respiratory response to acute (10 min) hypoxia, as measured by phrenic nerve activity, was determined in peripheral chemo-denervated cats.2. Hypoxia was induced by ventilating cats for 10 min at reduced inspired oxygen levels (inspired 02 fraction, FI°2 = 0-06-0-15). The degree of hypoxaemia was determined from an arterial blood sample and ranged from 'severe' (arterial 02 pressure, Pa,°< 26 Torr) to 'mild' (Pa, 02 > 35 Torr). The respiratory response was monitored for 1 h following return to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…sensi tive to C()2. are thought to be responsible for the initial fast phase of the response. With their denervation, the re sponse occurs at later time periods and has a more inert pattern [3], The removal of the glomus carotid results in complete disappearance of the response to hypoxia, al though this dogma is argued [25]. The response to hyper capnia in such a situation was found to be preserved, albeit of slowed magnitudes [26], In our investigations, the hemodynamic responses to the hypoxic challenge developed without any delay, in par allel to the respiratory responses.…”
Section: Discussionmentioning
confidence: 99%
“…sensi tive to C()2. are thought to be responsible for the initial fast phase of the response. With their denervation, the re sponse occurs at later time periods and has a more inert pattern [3], The removal of the glomus carotid results in complete disappearance of the response to hypoxia, al though this dogma is argued [25]. The response to hyper capnia in such a situation was found to be preserved, albeit of slowed magnitudes [26], In our investigations, the hemodynamic responses to the hypoxic challenge developed without any delay, in par allel to the respiratory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in peripheral chemoreceptor responsiveness 19,36,37 , central processing 18,20,38 , and the consequent efferent output 18 all effect the ventilatory response to hypoxia at altitude 16,17 . The further effect of changes in acid-base balance, as well as the complex nature of breathing at HA have been reviewed in detail 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the myriad of physiologic changes at HA related to the HVR [18][19][20] and HPV 21 , we hypothesized that resting SpO 2 at HA would correlate better than variability in HVR at SL to PASP at HA (i.e., by virtue of SpO 2 reflecting alveolar PO 2 and hence HPV). We also reasoned that chronic adaptation to HA, as seen in the Sherpa, would result in higher resting SpO 2 and lower PASP than that of lowlanders at HA.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this study was to locate the region of the mesencephalon responsible for the post-hypoxic inhibition of respiration which we have previously reported (Gallman & Millhorn, 1988). If hypoxia were acting directly upon neurones of the mesencephalon, it could, theoretically, operate in at least two manners.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition lasts up to 1 h or more following cessation of the hypoxic insult. Further investigation revealed that the mesencephalon is required, but that structures further rostral are not necessary, for expression of this long-lasting post-hypoxic inhibition (Gallman & Millhorn, 1988). Other investigators have similarly concluded that a suprapontine mechanism is involved in depression of respiration, particularly in fetal and neonatal animals (Dawes, Gardner, Johnston & Walker, 1983;Martin-Body & Johnston, 1988;Martin-Body, 1988).…”
Section: Introductionmentioning
confidence: 99%